Ways to improve the quality of housing-communal services - Shalbolova , U.Zh.; Yegemberdiyeva, S.M.; Khoich, A. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
Improving the quality of housing and communal services (HCS) is certainly relevant today, as the vector of development of the national economy of Kazakhstan is becoming more focused on improving the quality of life of the population. The quality of life of the population is crucial for the successful development of any country. The purpose of the study is to justify the functioning of urban housing and communal services and to develop mechanisms for its activation to improve the quality of services provided to the population. A detailed study has shown that there is a mismatch of living conditions with the main parameters of comfortable living: the presence of a certain proportion of dilapidated housing; low solvency of the population to improve housing conditions; low activity of introducing innovative technologies in the housing sector; low investment inflow due to low profitability in the housing sector. In order to determine the socio-economic prerequisites for the modernization of housing and communal services and urban economy conducted sociological surveys in the Kyzylorda region. The result of successful implementation of the improvement of the industry should be the effective functioning of enterprises of housing and communal services, ensuring their ability to provide the population with quality housing and communal services for a reasonable fee.